Impact of heat stress on female reproduction in farm animals: challenges and possible remedies (Bangladesh Journal of Animal Science, 2024)
Global warming poses significant challenges to agriculture, particularly within the livestock industry. Heat stress in animals refers to the physiological and metabolic distress experienced when environmental heat causes an animal’s body temperature to exceed its thermoneutral zone. Heat stress has a significant detrimental impact on reproductive outcomes, posing a direct threat to the profitability of livestock operations. Heat stress disrupts the normal hormonal balance essential for reproduction in female livestock, adversely affecting events of folliculogenesis and embryogenesis. As a result, the developmental competence of oocytes is compromised, which is crucial for successful fertilization and reproduction. Consequently, heat stress can lead to issues such as immature oocytes, atypical or sluggish embryonic development, silent estrus, and increased pregnancy loss causing a decline in reproductive rates and livestock owners face substantial financial losses. Despite using various cooling strategies, such as water sprinkler systems, cooling shades, and cooling devices, these measures are often insufficient to restore normal reproductive rates. Therefore, it is crucial to implement and explore novel strategies to enhance reproductive efficiency during periods of heat stress. Potential mitigation techniques include estrus synchronization, artificial insemination, hormonal alterations, embryo transfer, genetic engineering, sophisticated breeding strategies, the use of nutraceuticals, and changes in management practices. This review aims to consolidate recent findings on the adverse effects of heat stress on female reproduction, especially in tropical environments, and to evaluate potential strategies for improving summer fertility of livestock.Bangladesh Journal of Animal Science 53(3): 77-100, 2024